A review of the molecular mechanisms of acaricide resistance in mites and ticks - De Rouck, Sander; İnak, Emre; Dermauw, Wannes; Van Leeuwen, Thomas (Insect biochemistry and molecular biology, 2023)
The Arachnida subclass of Acari comprises many harmful pests that threaten agriculture as well as animal health, including herbivorous spider mites, the bee parasite Varroa, the poultry mite Dermanyssus and several species of ticks. Especially in agriculture, acaricides are often used intensively to minimize the damage they inflict, promoting the development of resistance. Beneficial predatory mites used in biological control are also subjected to acaricide selection in the field. The development and use of new genetic and genomic tools such as genome and transcriptome sequencing, bulked segregant analysis (QTL mapping), and reverse genetics via RNAi or CRISPR/Cas9, have greatly increased our understanding of the molecular genetic mechanisms of resistance in Acari, especially in the spider mite Tetranychus urticae which emerged as a model species. These new techniques allowed to uncover and validate new resistance mutations in a larger range of species. In addition, they provided an impetus to start elucidating more challenging questions on mechanisms of gene regulation of detoxification associated with resistance. [Display omitted] •Acari comprise several economically important mite and tick species.•Resistance development to acaricides is a serious worldwide problem.•New genomic tools have increased insights in resistance mechanisms.•Combinations of target-site and metabolic resistance can confer high resistance levels.•New detoxifying gene families were recently uncovered.•Gene regulation mechanisms in the context of resistance await further elucidation.